To multiply the polynomials \( (6x + 2)(4x - 3) \), we can use the distributive property (also known as the FOIL method for binomials).
-
Multiply the first terms: \[ 6x \cdot 4x = 24x^2 \]
-
Multiply the outer terms: \[ 6x \cdot (-3) = -18x \]
-
Multiply the inner terms: \[ 2 \cdot 4x = 8x \]
-
Multiply the last terms: \[ 2 \cdot (-3) = -6 \]
Now, we combine all these results: \[ 24x^2 - 18x + 8x - 6 \]
Next, combine the like terms \(-18x\) and \(8x\): \[ 24x^2 - 10x - 6 \]
Finally, the result in standard form is: \[ \boxed{24x^2 - 10x - 6} \]